Appointment of Brother Bernardo Oca FSC as vice president for external operations - De La Salle University, Manila (Animo Repository, 1993)
The Board of Trustees appointed Brother Bernardo Oca, FSC as Vice President for External Operations effective May 15, 1993, succeeding Dr. Wilfrido Villacorta who took his sabbatical leave in school year 1993-1994.